Mechanisms Ensuring Endothelial Junction Integrity Beyond VE-Cadherin - Duong, Cao Nguyen; Vestweber, Dietmar (Frontiers in Physiology, 2020)
Endothelial junctions provide blood and lymph vessel integrity and are essential for the formation of a vascular system. They control the extravasation of solutes, leukocytes and metastatic cells from blood vessels and the uptake of fluid and leukocytes into the lymphatic vascular system. A multitude of adhesion molecules mediate and control the integrity and permeability of endothelial junctions. VE-cadherin is arguably the most important adhesion molecule for the formation of vascular structures, and the stability of their junctions. Interestingly, despite this prominence, its elimination from junctions in the adult organism has different consequences in the vasculature of different organs, both for blood and lymph vessels. In addition, even in tissues where the lack of VE-cadherin leads to strong plasma leaks from venules, the physical integrity of endothelial junctions is preserved. Obviously, other adhesion molecules can compensate a loss of VE-cadherin and this review will discuss which other adhesive mechanisms contribute to the stability and regulation of endothelial junctions and cooperate with VE-cadherin in intact vessels. In addition to adhesion molecules, endothelial receptors will be discussed, which stimulate signaling processes that provide junction stability by modulating the actomyosin system, which reinforces tension of circumferential actin and dampens pulling forces of radial stress fibers. Finally, we will highlight most recent reports about the formation and control of the specialized button-like junctions of initial lymphatics, which represent the entry sites for fluid and cells into the lymphatic vascular system.